2005
DOI: 10.18267/j.pep.257
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Testing of New Keynesian Phillips Curve in Conditions of the Czech Republic in 1994 - 2003

Abstract: Abstract:New concepts have been presented in modelling of inflation dynamics recently, among others the new Keynesian Phillips curve (NKPC). There are several traditional ways of NKPC model validity testing, but none of them seems to be practically applicable in conditions of the Czech Republic. We tried to test the validity of NKPC on the basis of time series. For this purpose we applied an interesting non-traditional method proposed by Demery and Duck. This method does not rely on direct estimation of NKPC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In its basic cost-based form, the NKPC, stemming from the New Keynesian DSGE model, 3 is based on utility-maximizing households and profitmaximizing firms. 4 Only a fraction of firms (1 − θ) has a capacity to adjust prices in period t, where θ is a measure of price-stickiness, and future developments are discounted by a factor β. Opting for the cost-based NKPC in line with Galí and Gertler (1999), the NKPC in its simplest form can be expressed as: (1) where E t π t+1 are the inflation expectations observed at time t, mc t r real marginal cost with and ε t is a disturbance term. 5 Fuhrer (1997) and Galí and Gertler (1999), establishing an upgraded "hybrid" form of the NKPC argue that it is also necessary to take into consideration lagged inflation on top of the forward inflation expectations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In its basic cost-based form, the NKPC, stemming from the New Keynesian DSGE model, 3 is based on utility-maximizing households and profitmaximizing firms. 4 Only a fraction of firms (1 − θ) has a capacity to adjust prices in period t, where θ is a measure of price-stickiness, and future developments are discounted by a factor β. Opting for the cost-based NKPC in line with Galí and Gertler (1999), the NKPC in its simplest form can be expressed as: (1) where E t π t+1 are the inflation expectations observed at time t, mc t r real marginal cost with and ε t is a disturbance term. 5 Fuhrer (1997) and Galí and Gertler (1999), establishing an upgraded "hybrid" form of the NKPC argue that it is also necessary to take into consideration lagged inflation on top of the forward inflation expectations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous authors applied the NKPC in the context of the Czech Republic as well. One of the first were Arlt and Plašil (2005), employing a cointegration analysis of time series. The authors conclude that the NKPC model is not suitable in the conditions of the Czech Republic since it does not describe the inflation process sufficiently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In its basic cost-based form, the NKPC, stemming from the New Keynesian dynamic stochastic general equilibrium model, which is based on the utility maximizing households and profit-maximizing firms. 1 Only a fraction of firms (1 − θ) has a capacity to adjust prices in period t, where θ is a measure of price-stickiness, and future developments are discounted by a factor β. The NKPC can be expressed as:…”
Section: Literature Reviewmentioning
confidence: 99%
“…External shocks, in a form of the exchange rate deviation, translate through the transmission mechanism inevitably into domestic inflation via two channels, directly through the import prices and indirectly through the impact of the real exchange rate on real economy. When added to the model in compliance with Milučká (2014), the NKPC can be expressed as: 1 These firms assumed to be in monopolistic competition, are identical with the exception of differenced products and pricing history and face the same constant elasticity demand. 2 The coefficient λ depends negatively on θ and β.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tillmann (2009) made a similar point, saying that the model which is based on Calvo (1983) fails to grasp true forward-looking behaviors as well as previous research. The study by Arlt and Plasil (2005), which rejected GMM and employed co-integration analysis, backed up these claims. They found that NKPC does not match Czech Republican data and is a poor approximation of inflation dynamics.…”
Section: Introductionmentioning
confidence: 99%